Pre-operative and post-operative kinematic analysis in total knee arthroplasty. A pilot study - Di Benedetto, Paolo; Vidi, Daniele; Colombo, Andrea; Buttironi, Michele Mario; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
Introduction: Total knee replacement is the treatment of choice in knee osteoarthritis. Despite this, there is still a percentage of unsatisfied patients. Recently, prosthetic designs have been developed to improve the kinematics of the prosthetic knee. Materials and methods: Between June 2016 and November 2016 we enrolled 26 patients underwent to total knee arthroplasty divided in two groups (A and B) treated respectively with Journey 2 implant and the Attune impltant. Each patient was evaluated with functional scores (KOOS and KSS) and with kinematic analysis using the Bioval System. Results: In the group A, compared to the pre-operative, the flexion of the operated knees is significantly increased (31.27°±3.13° → 35.02°±2.1°) as well as that of the unoperated knee (34.34°±2.8° → 35.39°±3.5°). The pre/post-operative comparison of the muscles’ activation timing showed an improvement for the unoperated side, which is closed to the physiological pattern, while the operated side showed an incorrect activation of all the investigated muscles. Conclusions: The Journey 2 prosthesis seems to reach better results in rotational flexion, rotational freedom and muscles activation during free walking. Furthermore, it seems that with this prosthesis the patient can feel his “new prosthetic knee” more similar and closer to the physiological one. More studies are needed to confirm these results.